Study of Core Biopsies of the Prostate with Emphasis on Prostate Carcinoma Detection Rate, Its Quantification and Relation to Serum PSA Level - Kujur, Asha Lata; Pant, Vinita (Annals of Pathology and Laboratory Medicine, 2023)
Background According to the national cancer registries, there has been a noteworthy increase in the incidence and prevalence of prostate cancer in India in recent years. Elevated serum PSA level has been found to show a strong correlation with prostate cancer in multiple studies conducted worldwide. The aim of this study was (i) to determine the percentage positivity of prostate biopsies sent to our centre and compare it with national and international data (ii) to assess the number and percentage area of TRUS cores involved by adenocarcinoma and its correlation with serum PSA levels and Gleason grade. Material and methods A retrospective study was done in our histopathology laboratory wherein, 130 TRUS-guided biopsies received in proper fixative from different hospitals and clinics during a period of one year from 1st January 2021 to 31st December 2021, were evaluated for histopathological diagnosis. Proper detailed history and indication for biopsy were provided along with the requisition form. Statistical analysis was carried out on the data. Results A total of 130 biopsy samples were included in the study. Out of which 76 were malignant (58.5 %) and 54 were benign (41.5 %). It was proven that with an increase in total serum PSA level, there was an increase in the involvement of the number of cores by the tumour. A significant correlation was seen between the total serum PSA levels and involvement of cores by more than 50 per cent of tumour, proven by ANOVA and the Fischer exact test. It was also noted that the tumour volume showed a strong correlation with the grade group in accordance with the Modified Gleason grading system. Conclusion Total serum PSA level in conjunction with quantification of tumour provides valuable information to the clinician regarding the spread of tumour within the gland as well as the severity of the disease.Malaria and Dengue fever are the two most common arthropod-borne diseases in tropical countries like India, and endemic areas like Mangalore. Since they share a similar clinical presentation, identifying the hematological parameters, can help differentiate between patients of malaria and dengue fever and can help with its prognosis and early treatment. This study aims to find a link between diagnostic markers that are used to discriminate between the infections, occuring in malaria-endemic areas, such as Mangalore, Karnataka.